POTENSI RETRIBUSI PARKIR DI KABUPATEN PEKALONGAN - Choliq Sabana; Catur Ragil Sutrisno (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2013)
This study aims to analyze contribution of parking retribution for local revenue, the potential of parking retribution, and identifying the factors supporting and inhibiting acceptance roadside parking retribution general and special place. Research utilizes mixed method, which is research which utilize quantitative method  and  kualitative.  Observational  object  is  parking  retribution  at  common  wayside  and  special place parking retribution. There is location even research covers 135 dot park at common wayside and 50 dot park special places. The  analysis  shows  the  average  contribution  of  PAD  to  the  revenues  Pekalongan’s  Regency  7.92%, lower  than  the  average  contribution  of  PAD  to  Revenue  in  the  City  /  County  in  Indonesia  which amounted  to  12%.  Levies  a  major  contribution  to  regional  income,  ranging  from  71%.  Retribution parking  can  be  a  source  of  revenue  given  the  potential  for  the  development  of  demographic,  socio- economic, as well as the growth of vehicle ownership. Opportunities to increase revenue is still open considering parking retribution labor income is higher than the parking lot UMK of Central Java, and the growth of new parking base.  Keywords: potential, parking retribution, PAD.